Absence of a moderating effect of parent health literacy on Early Head Start enrollment and dental use. (16th April 2018) - Burgette, Jacqueline M.; Preisser, John S.; Weinberger, Morris; King, Rebecca S.; Lee, Jessica Y.; Rozier, R. Gary
Abstract: Objectives: To examine the moderating effect of parents' health literacy (HL) on the effectiveness of North Carolina Early Head Start (EHS) in improving children's dental use. Methods: Parents of 479 children enrolled in EHS and 699 Medicaid‐matched parent–child dyads were interviewed at baseline when children were approximately 10 months old and 24 months later. We used in‐person computer‐assisted, structured interviews to collect information on sociodemographic characteristics, dental use, and administer the Short Assessment of Health Literacy – Spanish and English (SAHL‐S&E). This quasi‐experimental study tested whether the interaction effect between EHS and parents' HL was associated with dental use. Logit (any use) and marginalized zero‐inflated negative binomial count models (number of dental visits) included random effects to account for clustering and controlled for baseline dental use, dental need, survey language, and a propensity score covariate. Results: Nineteen percent of parents in EHS had low literacy compared to 12 percent of parents in the non‐EHS group ( P < 0.01). The interaction term between EHS and parent's HL was not significant in the adjusted logit model (ratio of aORs 0.98, 95 percent CI: 0.43‐2.20) or the adjusted count model (ratio of aRRs 0.88, 95 percent CI: 0.72‐1.09). Conclusions: Parents in EHS had a higher prevalence of low HL compared to non‐EHS parents. Parents' HL did not moderate the relationship between EHS and child dental use, suggesting that EHS results in similar improvements in dental use regardless of parent's HL levels.